Macroeconomic report on Latin America and the Caribbean June 2012 (UN ECLAC SantiagoCL, 2012)
Presents an up-to-date analysis of the region's macroeconomic performance. Includes country notes which examine the economies of all the countries of Latin America and the Caribbean in 2011 and the first few months of 2012.
Keywords: ECONOMIC POLICY